2015
DOI: 10.1158/1078-0432.ccr-14-2031
|View full text |Cite
|
Sign up to set email alerts
|

Anti-S1P Antibody as a Novel Therapeutic Strategy for VEGFR TKI-Resistant Renal Cancer

Abstract: Purpose VEGFR2 tyrosine kinase inhibition (TKI) is a valuable treatment approach for patients with metastatic RCC. However, resistance to treatment is inevitable. Identification of novel targets could lead to better treatment for both patients with TKI naïve or resistant RCC. Experimental design In this study, we performed transcriptome analysis of VEGFR TKI resistant tumors in a murine model and discovered that the SPHK/S1P pathway is upregulated at the time of resistance. We tested S1P pathway inhibition u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 50 publications
2
72
3
Order By: Relevance
“…In retrospect, early imaging may preclude ascertainment of a delayed response to therapy, which is particularly relevant if sonepcizumab activity is driven through the immune-mediated mechanisms described above. 9 Ultimately, however, there was no observed association between S1P level and clinical outcome. 6 A second issue that could have mitigated the observed PFS of sonepcizumab is the extent of prior therapies rendered.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In retrospect, early imaging may preclude ascertainment of a delayed response to therapy, which is particularly relevant if sonepcizumab activity is driven through the immune-mediated mechanisms described above. 9 Ultimately, however, there was no observed association between S1P level and clinical outcome. 6 A second issue that could have mitigated the observed PFS of sonepcizumab is the extent of prior therapies rendered.…”
Section: Discussionmentioning
confidence: 88%
“…2 The pivotal phase 3 studies leading to the approval of these agents document a progression-free survival (PFS) in the range of 9 months to 12 months with each agent. 9 In von Hippel-Lindau (VHL)-deficient RCC xenograft models (786-O and A498), transcriptomic analysis demonstrated the increased expression of sphingosine kinase 1 (SPHK1), which catalyzes S1P production, in resistant tumors. [6][7][8] Although these agents have bested therapies previously approved in this setting such as everolimus, to the best of our knowledge few patients are cured of their disease and PFS (in phase 3 studies) ranges from 4.5 to 7.5 months.…”
Section: Introductionmentioning
confidence: 99%
“…and Sphingomab 65 may be useful adjunctive antitumor therapies. Several mechanisms are implicated in the observed effects on tumor cells and cancer outcome, including regulation of new blood vessel formation, direct cellular toxicity, and regulation of cellular survival and metabolism 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [37] have demonstrated that a sphingosine-1-phosphate (S1P) antibody induced S1P inhibition may be a new therapeutic strategy in patients with RCC and also in the batching of resistance to TKI therapy.…”
Section: Anti-s1p Mabmentioning
confidence: 99%